Österreich 2025: Arbeitszeitverteilung in Österreich. Analyse und Optionen aus Sicht der Arbeitnehmerinnen und Arbeitnehmer - Ulrike Huemer; Julia Bock-Schappelwein; Ulrike Famira-Mühlberger; Hedwig Lutz; Christine Mayrhuber (Verlag des ÖGB GmbH, 2017)
Die empirische Evidenz zur Verteilung der Arbeitszeit unselbstständig Beschäftigter in Österreich zeigt eine hohe Heterogenität, insbesondere zwischen Frauen und Männern (Gender-Time-Gap). Grund dafür sind traditionelle Rollenbilder sowie die ungleiche Verteilung der Hausarbeit und der Betreuung von Kindern und Pflegebedürftigen. Die vorliegende Studie liefert arbeitszeitbezogene Ansatzpunkte zur Förderung einer ausgeglichenen Verteilung der Erwerbsarbeitszeit von Frauen und Männern, ebenso wie Maßnahmen für spezifische Lebensphasen, die eine Anpassung der individuellen Erwerbsarbeitszeit zur Vereinbarkeit von Beruf und außerberuflichen Verpflichtungen bzw. Interessen ermöglichen. – – The empirical evidence for the distribution of the working hours of dependent workers in Austria shows a high heterogeneity, especially between women and men (gender time gap). While women spend an average more time per week on unpaid activities than men, men are on average a full-time day per week (8.2 hours) longer in paid employment than women. The significant difference in average weekly working hours (men 39.8 and women 31.6 hours) is primarily due to the fact that almost half of women (49.4%) work part-time and many men work overtime. The reason for this is traditional gender roles, as well as the uneven distribution of domestic work and the care of children and dependent persons. For example, in couples with children under the age of 15, the modified breadwinner model dominates: the man is full-time working, the woman part-time. At the same time, about a quarter of the employed is unsatisfied with their actual weekly working hours: on average women prefer working more hours a week, men less. With increasing age, the distance between preferred and realized weekly working hours increases. The study shows working-time approaches to promote a balanced distribution of the working time of women and men over their working lives, as well as measures for specific life stages, which allow an adaptation of the individual working time to reconcile work and non-work commitments or interests.
Keywords: 300; Wahlarbeitszeit; Freizeitoption; Gender-Time-Gap; Arbeitsvolumen; Überstundenpauschalierung; Arbeitszeitverteilung; Betreuungspflichten; Erwerbsarbeitszeit; Alleinverdiener-Modell; Arbeitszeitprofil; Zuverdiener-Modell; Normalarbeitszeit; Arbeitszeitlücke; Lebensphasenmodell